Status quo and research progress of Traditional Chinese Medicine professional training based on the Traditional Chinese Medicine nursing training base (以中医护士培训基地为依托的中医护理专业化培训现状及研究进展) - WANG Yuan (王媛); WANG Bei (王蓓); WANG Fengmei (王凤美); ZHANG Xixia (章细霞) (中西医结合护理)
Starting from the Status quo and research progress of Traditional Chinese Medicine professional training, this paper reviews studies on training pattern, training content and methods, training quality evaluation, training institutions and teaching staff construction, specialist Training and clinical practice in the Traditional Chinese Medicine nursing training base, and provides reference for training management of Traditional Chinese Medicine nursing training base and domestic policy making of Traditional Chinese Medicine nursing specialists training. (本文从中医护理专业化培训现状和研究进展方面切入, 梳理以中医护士培训基地为依托的中医护理专业化培训模式、培训内容和方法、培训质量评价、培训机构和师资队伍建设、专科培训与临床实践结合五个方面的现状与发展, 为国内中医护士培训基地的培训管理和中医护理专业化培训政策及方法制定提供参考。)